2013
DOI: 10.5534/wjmh.2013.31.3.254
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Report on the Safety of a New Herbal Formula and Its Effect on Sperm Quality

Abstract: PurposeMale infertility is a serious problem, and its prevalence has been increasing. Therefore, we investigated the safety of a new herbal formula and its effects on sperm quality.Materials and MethodsAn in vitro cytotoxicity test in TM3 Leydig cells was performed to evaluate cell viability after administration of five types of herbs separately and of a new herbal formula containing these five. An in vivo test in male mice was performed to evaluate the influence of the new herbal formula on the reproductive o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 29 publications
1
26
0
Order By: Relevance
“…Preliminary in vivo results have also shown that these five herbs improve sperm count and activity. 15 This effect might be a result of their anti-oxidative properties, which help restore the imbalance of excessive levels of reactive oxygen species.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary in vivo results have also shown that these five herbs improve sperm count and activity. 15 This effect might be a result of their anti-oxidative properties, which help restore the imbalance of excessive levels of reactive oxygen species.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, A. gigas is known to exert antibacterial and antiamnestic effects as well to induce inhibitory effects against acetylcholinesterase, depression of cardiac contraction, and activation of protein kinase C [2,7,13,14,25]. Several herbs that were used in traditional medicine demonstrated antioxidant or free radical scavenging activities [8]. Further, some of the herbal supplements with antioxidant properties exhibited a beneficial effect on the sperm function.…”
Section: Angelica Gigas Nakai (A Gigas) Is a Korean Traditionalmentioning
confidence: 99%
“…Further, some of the herbal supplements with antioxidant properties exhibited a beneficial effect on the sperm function. These showed antioxidant activities in various diseases besides male infertility causing decreased sperm quality [8].…”
Section: Angelica Gigas Nakai (A Gigas) Is a Korean Traditionalmentioning
confidence: 99%
“…Several herb supplements with antioxidant properties are known to have a beneficial effect in various diseases with increased sperm quality 13 . in the present study, we examined the effect of the cultivated wild ginseng extracts (CWge) on the number of sperm cells in rat treated with or without BPa compared it against that observed upon treatment with BPa.…”
mentioning
confidence: 99%